2014
DOI: 10.6000/2292-2598.2014.02.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Algebra Underlying Special Education Teachers’ and Psychology Students’ Attitudes Towards School Inclusion of People with Intellectual Disability

Abstract: Attitudes towards regular school inclusion of people with intellectual disabilities (ID) are affected by factors such as disability severity, educational level, and teacher experience. Nevertheless, the ways that teachers integrate these factors to form inclusion judgments remains unclear. The current paper explores what systematic cognitive algebra rules are used to cognitively integrate this set of inclusion factors by special education teachers and psychology students. To do so, 469 special education teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Furthermore, other research findings have pointed out that cognitive rules to form expectations of success for the job training of PWID could vary depending on the evaluated educational level. For example, unlike the results obtained here, research considering job training of PWID at the elementary school level (preschool, primary school, and high school) has suggested that judgments of success are based on information integration summative cognitive rules in success [22]. This could be the case because job training has a greater temporal proximity to independent living than it does to early education.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, other research findings have pointed out that cognitive rules to form expectations of success for the job training of PWID could vary depending on the evaluated educational level. For example, unlike the results obtained here, research considering job training of PWID at the elementary school level (preschool, primary school, and high school) has suggested that judgments of success are based on information integration summative cognitive rules in success [22]. This could be the case because job training has a greater temporal proximity to independent living than it does to early education.…”
Section: Discussioncontrasting
confidence: 81%
“…Overall, results suggest that when PWID are training for a job, teachers and students in the special education system consider that successful job training depends more on individual than on contextual factors. It would be very interesting to explore other contextual variables as suggested in previous research (e.g., teaching variables [22]). Furthermore, other research findings have pointed out that cognitive rules to form expectations of success for the job training of PWID could vary depending on the evaluated educational level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By considering this cognitive specification schema, this research aims to determine the way students take the decision to cheat by analysing psychological valuation (V) as well as to cognitively specify algebraic integration of information (I operator) in order to put under scrutiny the observed cheating behaviour (R). The cognitive algebra paradigm has been used to explore a variety of human behaviour domains (Castro, Morales, Lopez, Olivares, & Masip, 2018;Esterle, Munoz-Sastre, & Mullet, 2008;Falconi & Mullet, 2003;Herve, Mullet, & Sorum, 2004;Morales, 2012;Morales-Martinez, Lopez-Ramirez, Esterle, Munoz-Sastre, & Mullet, 2010), including special education (e.g., Morales, Lopez, Villarreal-Trevino, Montalvo, Mezquita-Hoyos, & Castro-Sanchez, 2014), technical education for work settings (e.g., Morales-Martinez, Lopez-Ramirez, Villarreal-Trevino, & Mezquita-Hoyos, 2015) and academic self-efficacy in middle education (e.g., Briones-Rodriguez, Morales-Martinez, Santos-Alcantara, Lopez-Ramirez, & Urdiales-Ibarra, 2016) and higher education (e.g., Villarreal-Trevino, Villarreal-Lozano, Morales-Martinez, Lopez-Ramirez, & Flores-Moreno, 2017). However, academic dishonesty has never been explored from an IIT perspective, and the goal of this research is to introduce this approach in the field of academic dishonest behaviour by answering the question: What are the cognitive information integration mechanisms that might lead to academic cheating?…”
Section: Information Integration Theory As a Cognitive Methods For Expmentioning
confidence: 99%
“…Applying the IIT principles to the educational field, it is possible to observe the information selection and integration processes in the teachers' and learners' minds that allow them to judge their circumstances and make academic decisions. For example, in Mexico, special education teachers were found to use a summative cognitive rule to judge the probability that a person with an intellectual disability (ID) would be successfully integrated into mainstream education (Morales et al, 2014). On the other hand, they used a multiplicative cognitive rule to judge the probability that a person with ID could learn a skill through technical training (Morales et al, 2015).…”
Section: Present Studymentioning
confidence: 99%